Sulforaphane suppresses cell growth and collagen expression of keloid fibroblasts. Issue 2 (20th February 2017) - Kawarazaki, Ayako; Horinaka, Mano; Yasuda, Shusuke; Numajiri, Toshiaki; Nishino, Kenichi; Sakai, Toshiyuki
Abstract: Keloids are fibroproliferative diseases characterized by the accumulation of an extracellular matrix including collagen. Various growth factors, or cytokines, and their receptors are overexpressed in keloids, and they are expected to be therapy targets. Sulforaphane, a dietary isothiocyanate, has recently shown anti‐tumor, anti‐inflammatory, and anti‐fibrotic properties. In this study, we found that sulforaphane inhibited cell growth and reduced collagen at the mRNA and protein levels in keloid fibroblasts. Moreover, sulforaphane markedly suppressed the expression of IL‐6 and α‐SMA and inhibited Stat3 and Smad3 signaling pathways in keloid fibroblast KF112 cells. Sulforaphane induced G2/M cell‐cycle arrest with the induction of p21 in KF112 cells. In addition, sulforaphane inhibited cell growth and suppressed the expression of collagen in keloid fibroblasts under a coculture with peripheral blood mononuclear cells. Furthermore, sulforaphane suppressed IL‐6, Stat3, and Smad3 signaling in the coculture system. This study suggests that sulforaphane may be a novel keloid treatment.